Invasive breast carcinoma with granulomatous response and deposition of unusual amyloid. Issue 10 (October 1992) - Santini, D; Pasquinelli, G; Alberghini, M; Martinelli, G N; Taffurelli, M
Abstract : AIMS: To report an unusual case of invasive breast ductal carcinoma associated with non-caseating epithelioid granuloma and unusual deposition of amyloid. METHODS: Formalin fixed, paraffin wax embedded tissue from breast and lymph nodes were stained with a variety of methods. Representative tissue fragments were sampled and fixed in 2.5% buffered glutaraldehyde, postfixed in 1% osmium tetroxide, dehydrated and embedded in Araldite. Thin sections were viewed under a Phillips 400T transmission electron microscope. RESULTS: Multinucleated giant Langhans' cells were found in the granulomatas tissue in both breast carcinoma and metastatic axillary lymph node carcinoma. Electron microscopic examination showed "tubular" amyloid deposition intermingled with invasive carcinoma and granuloma. "Tubular amyloid" was characterised by a mesh of non-branching curving fibrils with hollow profiles. These tended to be located in the cell membranes. CONCLUSION: The presence of an epithelioid granulomatous reaction and deposition of "tubular" amyloid in an invasive breast carcinoma could be related to an abnormal immunological response.